¿Cambio de paradigma en las finanzas internacionales? - Iturria, Juan Pablo; Soldera, Pedro Osmar (Universidad Nacional de Villa María, 2021)
During the course of the last five decades, we have increasingly incorporated within the heterogeneous group of our globalized society, the greater prominence and sophistication of international finance within the usual transactions between traditional commercial actors. Accelerated from the great deregulations of the circulation of capital typical of the dynamics of capitalism in its current financialized version, the vital operational role of banks as scaffolding of this colossal structure has historically been invisible to the general public. It is of vital importance to understand this paradigm that tends to the current concentration, to relate how the interaction of these institutions to manage the nominal flow of International Trade perpetuates the US geopolitical hegemony. However, the appearance of certain anomalies in the main engines that feed this present scenario driven by the emerging powers, such as the questioning of a monopoly system of international transfers, arbitrary international reference rates and the emergence of state electronic currencies, make foresee a change in the medium term of the model currently installed.